Analisis Strategi Pelaku UMKM Dalam Mengembangkan Usaha Pada Perekonomian Daerah (Studi Kasus Usaha Budidaya Itik “Sumber Rejeki” di Desa Tawangrejo Kecamatan Turi Kabupaten Lamongan) - Fajar Try Leksono (Universitas Negeri Malang, 2015)
Farming activity is not uncommon anymore for Indonesian people, especially for duck farming. Duck farming businesses are increasingly in demand as an alternative source of income for people in rural and peri-urban. Tawangrejo village Turi district, is one of the village in Lamongan in which the majority of communities maintain a duck as a profit-making business. This research approach is qualitative approach. The subjects were a group of SMEs business of Sumber Rejeki. These results indicate that the production strategies conducted by Sumber Rejeki group still basic and not in accordance with the existing potential in the Sumber Rejeki group itself as the potential of ecosystems that support, as well as high social capital. Limited land and the multiple roles of the housewife as the constrain is a major problem. Other obstacles that could hamper the productivity of farmers in the Sumber Rejeki group include limited capital, limited human resources, networking, as well as duck diseases. SMEs’ activitie of Sumber Rejeki is a form of local economic development through the utilization of the agricultural sector and the empowerment of women. The business development strategies that could be advised of the researcher are: (1) the ease of access to capital, (2) infrastructure support, (3) development of business scale, (4) development of business networks, marketing and business partnership, and (5) development of human resources.Keywords: Production, Constraint, Developing Strategy